Role of histamine in the aetiology of byssinosis. II. Lung histamine concentrations in guinea pigs chronically exposed to cotton and flax dusts. Issue 2 (May 1984) - Noweir, M H; Abdel-Kader, H M; Makar, A
Abstract : Data presented in this study support the finding that cotton and flax dusts contain agents which potentiate the formation or accumulation of histamine or both in the lungs of guinea pigs exposed to dust, and that such agents are present at much higher levels in cotton dust than in flax dust. The potentiating effect may be through the recruitment of mast cells into the lung. Both cotton and flax dusts contain methylating enzyme inhibitory agents, whereas cotton dust also contains agents that inhibit histaminase activity; flax dust contains agents potentiating histamine activity. These agents working together result in the accumulation or depletion of histamine observed in the different groups of animals exposed to either cotton or flax dust in this study.